Lamentations, Robin A. Parry : book review - Usue, Emmanuel Ordue (Old Testament essays, 2012)
Parry has made a wonderful theological and exegetical contribution on the book of "Lamentations" to a Commentary series titled: "The Two Horizons Old Testament Commentary." In this book, Parry offers a paragraph-by-paragraph engagement with the text of Lamentations which is deliberately theological in focus. Parry outlines two tasks for readers of the book of Lamentations. First, that readers of the book of Lamentations should hear the distinctive pre-Christian theological voice of Lamentations. Secondly, that they should hear how the acoustics change when that voice is heard in the cathedral of Christ. In other words, people must not read Lamentations as if Jesus had not come.